2019
DOI: 10.1505/146554819825863753
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Livelihood Practices, Strategies and Dependence on Bushmeat in Two Provinces in Gabon

Abstract: Traditional, forest resource-dependent livelihoods face multiple challenges. In Gabon, bushmeat provides food and income for rural communities. This study investigates how villagers believe livelihood practices and dependence on bushmeat changed over the last decade and if alternative income and food generating strategies can be sustainable. Our results show that remote villages near Moukalaba Doudou National Park hardly changed practices. Less remote villages near Tchibanga experienced declining hunting reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Current prohibitions are already difficult to enforce. 27 , 28 , 29 Tropical SW Ghana Moderate Moderate Moderate Food system could potentially adapt overall; however severe impacts would be felt by some. Economic shocks may be the biggest risk, for female traders/wholesalers.…”
Section: Resultsmentioning
confidence: 99%
“…Current prohibitions are already difficult to enforce. 27 , 28 , 29 Tropical SW Ghana Moderate Moderate Moderate Food system could potentially adapt overall; however severe impacts would be felt by some. Economic shocks may be the biggest risk, for female traders/wholesalers.…”
Section: Resultsmentioning
confidence: 99%
“…Socio-economic surveys showed that in 2010 around 12% of all Gabonese families were likely to be directly involved in hunting and 11% were involved in some way in the wild meat trade (Abernethy and Ndong Obiang 2010 ). Although, as in Ghana, there is evidence of overall declining participation due to urbanisation (Fairet et al 2014 ; van Gils et al 2019 ), unlike Ghana, there are indications that seasonal workers take up hunting when moving home from the city during short breaks. In their survey of wild meat markets in Gamba, Thibault and Blaney ( 2003 ) suggested that the observed peaks in wild meat trade volumes in June and December were correlated with seasonal workers returning home.…”
Section: Applying the Framework In The Context Of Two Case Studies: Gmentioning
confidence: 99%
“…Local people collect firewood and other natural resources such as edible wild plants, mushrooms, and honey from the forest and savannah. Hunting and fishing are supplementary subsistence activities to obtain animal protein (Matsuura & Moussavou, 2015; Van Gils et al, 2019). Owing to the area’s distance from the city, opportunities for cash income from the sale of agricultural crops (mainly plantain bananas) and forest products are scarce.…”
Section: Methodsmentioning
confidence: 99%